Profit obtained from the violation of personality rights (Revista do Tribunal Regional Federal da 3ª Região, 2024)
This article aims to demonstrate that the Brazilian legal system imposes on the offender a duty to repay the profit obtained through an offense against personality rights. In this sense, it aims to demonstrate that this duty of restitution can be imposed based on the institute of unjust enrichment, as well as that there are criteria for quantifying the amount to be repaid and that such restitution claim can be combined with the reparatory claim. The legal destination of the economic advantage obtained through rights violation is a issue that has challenged the doctrine of various systems. The debates in US law on the "disgorgement of profits" have contributed to the evolution of this issue, as also have notable studies in Portugal and, more recently, in Brazil. One of the fundamental points about this obligation to return unjust profits is to define its legal basis in each law. In Brazil, the understanding has been that the institute of unjust enrichment would fulfill this role. This definition allows progress to be made on the subject of unjust profit, establishing criteria for quantifying the economic advantage to be returned by the offender, insofar as unjust enrichment does not have a punitive or reparatory nature, a circumstance that allows limits to be set for determining the object of restitution, with examples of these criteria being habitual remuneration and causality.
Keywords: Unjust profit; Personality rights; Duty of restitution; Unjust enrichment; Quantification